Survival of dogs with myxomatous mitral valve disease administered preclinical pimobendan in comparison to pimobendan-naïve dogs from the onset of congestive heart failure - G. McAulay; M. Hills; J. Dukes-McEwan; E. Dutton; A. Jakubczak; D. Singleton; E. Bode; W. Yangwanitset; M. Hezzell (Journal of Veterinary Cardiology, 2026)

Understanding Postpartum Mothers’ Perspectives of Chrononutrition Approaches: A Qualitative Study - Elizabeth N. Davis; Zena A. Patel; Christie Kirchoff; Courtney M. Peterson; Gareth R. Dutton; Erin Contratto; Camille R. Schneider-Worthington (Journal of the Academy of Nutrition and Dietetics, 2026)

Diverse and perennial cropping systems alter microbial community structure and increase the spatial variability of microbial diversity and functioning under a precipitation gradient - Deniz Lara Dutton; Mary-Cathrine Leewis; Visveshwar Senthilkumaran; Cynthia M. Kallenbach (Applied Soil Ecology, 2026)

ShellBank: traceability toolkit and global database of marine turtle DNA - Michael P. Jensen; Greta J. Frankham; Carla Alonso O’Friel; Erin L. LaCasella; Kelly I. Morgan; Maftuna Sola; Lucy M. I. Webster; Peter H. Dutton; Christine A. Madden (Frontiers in Marine Science, 2026)
Effective conservation and enforcement strategies for marine turtles depend on understanding population structure, connectivity, and the geographic origins of turtles impacted by threats such as bycatch, overexploitation, and illegal trade. However, mitochondrial DNA (mtDNA) data remain fragmented across studies, with inconsistent sequence lengths, haplotype nomenclature, and metadata standards limiting their application in conservation, management, and wildlife forensics. To address these challenges, we developed ShellBank, a global marine turtle genetic traceability toolkit and open-access mtDNA database that consolidates and standardizes more than 20,000 mtDNA control-region sequences from published literature and verified contributed datasets. The platform harmonizes sequence lengths, haplotype nomenclature, and associated metadata, and provides tools to search haplotypes, access population-level baselines, extract frequency tables for Mixed Stock Analysis (MSA), and explore connectivity among nesting, in-water, and trade datasets. We demonstrate its utility through two case studies. First, mtDNA from a tortoiseshell seizure in the United Kingdom was compared against the ShellBank baseline, identifying likely source rookeries in the Eastern Caribbean and highlighting priority sampling gaps. Second, reanalysis of a hawksbill turtle foraging aggregation on the Great Barrier Reef using an expanded reference baseline substantially altered previous stock assignment estimates, corroborated flipper-tag and satellite-tracking data, and confirmed multi-stock connectivity across the western Pacific. By centralizing and standardizing global marine turtle mtDNA data, ShellBank improves the resolution, accuracy, transparency, and application of genetic traceability for conservation, management, and enforcement, strengthening the ability of researchers, managers, decision-makers, and enforcement agencies to identify source regions, detect population-level impacts, understand ecological connectivity, and guide evidence-based conservation actions.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Multi-scale observations during the 2024 mass coral bleaching event on Heron Reef, Australia - Devin A. Rowell; Nicholas M. Hammerman; Kirsten M. Golding; Tania Marie Kenyon; Zoe Meziere; Courtney Morgans; Kristen Taylor Brown; Faye F. Diederiks; David E. Carrasco Rivera; Karen Eigeland; Roima Paewai-Huggins; Kathryn Markey; et al. (Marine Biology, 2026)

Expanding the boundaries: regional connectivity in green turtle (Chelonia mydas) populations across Micronesia - Michael P. Jensen; Erin L. LaCasella; Donald R. Kobayashi; Amy Frey; Tammy M. Summers; Jessy R. Hapdei; George H. Balazs; Shawn K. K. Murakawa; T. Todd Jones; Summer L. Martin; Alexander R. Gaos; Peter H. Dutton (Frontiers in Marine Science, 2025)
The importance of ocean currents in influencing the connectivity and dispersal of marine megafauna, including sea turtles, is becoming increasingly recognized. However, more comprehensive studies are needed on how these currents impact the genetic makeup and connectivity of green turtle Chelonia mydas (Linnaeus, 1758) populations in the Pacific Islands region. To address this gap, our study conducted genetic analyses of green turtles in foraging grounds from four Micronesian sites and predictive modelling of hatchling dispersal patterns based on ocean currents to explore connectivity between foraging grounds and rookeries across Micronesia. We analyzed mitochondrial DNA (mtDNA) haplotype frequencies from newly collected and published data. We used Bayesian mixed stock analysis (MSA) to estimate the relative proportion of turtles from different Management Units (MUs) within the foraging grounds. Our ocean current simulations predicted hatchling dispersal trajectories, revealing how passive drift may facilitate wide-ranging dispersal and connectivity among distant foraging and nesting sites. Across the four Micronesian foraging grounds, the MSA revealed varying contributions from different rookeries, with some turtles exhibiting rare, long-distance dispersal traits. Our study highlights the intricate relationship between oceanic currents and the spatial dynamics of green turtles across the Pacific. Our findings offer essential insights into the conservation and management of green turtles by highlighting the role of oceanic currents in shaping population connectivity. Future research should focus on expanding genetic analyses and refining ocean drift simulations to enhance our understanding of marine megafauna migration and inform regional conservation strategies effectively.

Population structure and genetic diversity of leatherback turtles (Dermochelys coriacea) in Bird’s Head Seascape, Papua-Indonesia - Abdul Hamid A. Toha; Deasy Lontoh; Fitryanti Pakiding; Andhika P. Prasetyo; Lisa M. Komoroske; Peter H. Dutton (Frontiers in Marine Science, 2025)
Leatherback (Dermochelys coriacea) populations are endangered globally and there is a need to better understand their genetic diversity and structure in order to inform conservation efforts. Most nesting in the western Pacific is concentrated in the Bird’s Head Seascape (BHS) region of West Papua, Indonesia. Previous genetic assessment based on limited mtDNA sequences inadequately represented the demographic complexity that is now evident for West Papua leatherbacks. In this study, we quantified the genetic diversity, connectivity and structure for leatherback populations in the BHS by integrating nuclear and mitochondrial (mt) DNA data. We compared 763-bp sequences of the mtDNA control region and data from 17 microsatellite loci at two beaches, Jeen Yessa (JY) and Jeen Syuab (JS) that represent temporally separated nesting populations. We then leveraged reduced-representation (RAD-capture) and whole genome resequencing approaches to generate genome-wide SNPs. We detected low genetic diversity for all datatypes. A total of 11 mtDNA haplotypes were identified, including two new haplotypes and three previously reported from Atlantic populations. Pairwise tests of haplotype and genotype (microsatellite) frequencies found no evidence of structure between the JY (boreal summer) and JS (boreal winter) populations. Furthermore, admixture and principal components analyses of genomic SNP datasets did not identify any clear genetic structure. These results suggest that the BH leatherbacks represent a single genetic stock based on current criteria for defining population Management Units for sea turtles. This study provides the basis for further population structure assessment that includes other nesting sites in Indonesia and the broader western Pacific.

Integrating the Bright and Dark Sides of Aquatic Resource Subsidies—A Synthesis - Cornelia W. Twining; Andreu Blanco; Christopher Dutton; Martin J. Kainz; Eric Harvey; Carmen Kowarik; Johanna M. Kraus; Dominik Martin‐Creuzburg; Tarn Preet Parmar; N. Roxanna Razavi; Nicole Richoux; Gregoire Saboret; et al. (Ecology Letters, 2025)
Aquatic and terrestrial ecosystems are linked through the reciprocal exchange of materials and organisms. Aquatic‐to‐terrestrial subsidies are relatively small in most terrestrial ecosystems, but they can provide high contents of limiting resources that increase consumer fitness and ecosystem production. However, they also may carry significant contaminant loads, particularly in anthropogenically impacted watersheds. Global change processes, including land use change, climate change and biodiversity declines, are altering the quantity and quality of aquatic subsidies, potentially shifting the balance of costs and benefits of aquatic subsidies for terrestrial consumers. Many global change processes interact and impact both the bright and dark sides of aquatic subsidies simultaneously, highlighting the need for future integrative research that bridges ecosystem as well as disciplinary boundaries. We identify key research priorities, including increased quantification of the spatiotemporal variability in aquatic subsidies across a range of ecosystems, greater understanding of the landscape‐scale extent of aquatic subsidy impacts and deeper exploration of the relative costs and benefits of aquatic subsidies for consumers.

Isolation of a CTX-M-55 (ESBL)-Producing Escherichia coli Strain of the Global ST6448 Clone from a Captive Orangutan in the USA - Carly M. Smith; Melissa Anacker; Durward L. Bevis; Nicole A. M. Dutton; Dan Powell; Richard William McLaughlin (Current Microbiology, 2024)

Co-designing a multi-criteria approach to ranking hazards to and from Australia’s emerging offshore blue economy - Mischa P. Turschwell; Christopher J. Brown; Myriam Lacharité; Jess Melbourne-Thomas; Keith R. Hayes; Rodrigo H. Bustamante; Jeffrey M. Dambacher; Karen Evans; Pedro Fidelman; Darla Hatton MacDonald; Ingrid Van Putten; Graham Wood; et al. (Environmental Science & Policy, 2023)

Differences in Left Ventricular Enlargement Secondary to Chronic Volume Loading Between English Springer Spaniels and Two Similar Sporting Breeds - D. Dickson; E. Bode; C. Linney; E. Dutton; D. Caivano; T. Bispo; J. Harris; M. Rishniw (Journal of Veterinary Cardiology, 2023)

Population structure of Pacific green turtles: a new perspective from microsatellite DNA variation - Suzanne E. Roden; John B. Horne; Michael P. Jensen; Nancy N. FitzSimmons; George H. Balazs; Richard Farman; Jennifer Cruce Horeg; Jessy Hapdei; Maike Heidemeyer; T. Todd Jones; Lisa M. Komoroske; Colin J. Limpus; et al. (Frontiers in Marine Science, 2023)
This study builds upon the current understanding of green turtle population genetic structure in the Pacific that has largely been based on mitochondrial DNA (mtDNA), by examining nuclear DNA (nDNA) diversity, regional connectivity, and male-mediated gene flow. A total of 1,111 nesting green turtle samples were analyzed with 10 microsatellite markers from 20 Pacific rookeries. Population differentiation (F ST ) was significant (p <0.05) in all but 8 of 190 pairwise rookery comparisons. Pairwise F ST values and discriminant analysis of principal components (DAPC) revealed a defined East-West split consistent with mtDNA studies. Additionally, isolation-by-distance was evaluated with estimated effective migration surfaces (EEMS). The data indicated structure throughout the Pacific rookeries largely in agreement with stock structure defined by mtDNA studies, except for some areas on the Central American and Australian continental shelves, providing evidence of possible male-mediated gene flow. The series of analyses performed did indicate that male-mediated gene flow has likely occurred where breeding migration corridors of separate populations overlap with courtship areas. This may occur primarily along the margins of continents, including along Mexico and Central America in the East Pacific. Our study provides an ocean-wide baseline nDNA dataset for green turtle rookeries in the Pacific and reexamines the current thinking regarding the role of male turtles in the population dynamics of management units (MU) and to what extent nuclear gene flow occurs among designated MUs.

Seagrass Abundance Predicts Surficial Soil Organic Carbon Stocks Across the Range of Thalassia testudinum in the Western North Atlantic - James W. Fourqurean; Justin E. Campbell; O. Kennedy Rhoades; Calvin J. Munson; Johannes R. Krause; Andrew H. Altieri; James G. Douglass; Kenneth L. Heck; Valerie J. Paul; Anna R. Armitage; Savanna C. Barry; Enrique Bethel; et al. (Estuaries and Coasts, 2023)

United States Gulf of Mexico Waters provide important nursery habitat for Mexico’s Green turtle nesting populations - Brian M. Shamblin; Kristen M. Hart; Margaret M. Lamont; Donna J. Shaver; Peter H. Dutton; Erin L. LaCasella; Campbell J. Nairn (Frontiers in Marine Science, 2023)
Resolving natal populations for juvenile green turtles is challenging given their potential for extensive dispersal during the oceanic stage and ontogenetic shifts among nursery habitats. Mitochondrial DNA markers have elucidated patterns of connectivity between green turtle nesting populations (rookeries) and juvenile foraging aggregations. However, missing rookery baseline data and haplotype sharing among populations have often impeded inferences, including estimating origins of Gulf of Mexico juveniles. Here, we assessed genetic structure among seven foraging aggregations spanning southern Texas (TX) to southwestern Florida (SWFL), including Port Fourchon, Louisiana (LA); a surface-pelagic aggregation (SP) offshore of Louisiana and Florida; Santa Rosa Island, Florida (SRI); St. Joseph Bay, Florida (SJB); and the Big Bend region, Florida (BB). We estimated source contributions to aggregations with novel genetic data (excluding SP and BB) using a Bayesian many-to-one mixed stock analysis (MSA) approach. Haplotype frequencies for western (TX, LA, SP, SRI) and eastern (SJB, BB, SWFL) aggregations were significantly differentiated. The largest shift in haplotype frequencies between proximal nursery sites occurred between SRI and SJB, separated by only 150 km, highlighting the lack of a geographic yardstick for predicting genetic structure. In contrast to previous MSA results, there was no signal of Florida juveniles at any foraging site. Mexican contributions dominated in all aggregations, with strong connectivity between western Bay of Campeche (Tamaulipas/Veracruz) rookeries and western foraging aggregations. MSA indicated more diverse Mexican origins for eastern aggregations, with larger inputs from the eastern Bay of Campeche (Campeche/Yucatán), Campeche Bank, and Quintana Roo rookeries. These results demonstrate the significance of the Gulf of Mexico coast and offshore waters of the United States as important nursery habitat for green turtles of Mexican origin and highlight the need for international coordination for management of these populations.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Alternative Biogeochemical States of River Pools Mediated by Hippo Use and Flow Variability - Christopher L. Dutton; Amanda L. Subalusky; Stephen K. Hamilton; Ella C. Bayer; Laban Njoroge; Emma J. Rosi; David M. Post (Ecosystems, 2021)

Single nucleotide polymorphism markers for genotyping hawksbill turtles (Eretmochelys imbricata) - Shreya M. Banerjee; Lisa M. Komoroske; Amy Frey; Brittany Hancock-Hanser; Phillip A. Morin; Frederick I. Archer; Suzanne Roden; Alexander Gaos; Michael J. Liles; Peter H. Dutton (Conservation Genetics Resources, 2020)

An updated geographic distribution of Myxobolus cerebralis (Hofer, 1903) (Bivalvulida: Myxobolidae) and the first diagnosed case of whirling disease in wild‐caught trout in the south‐eastern United States - Steven P. Ksepka; Jacob M. Rash; Brandon L. Simcox; Doug A. Besler; Haley R. Dutton; Micah B. Warren; Stephen A. Bullard (Journal of Fish Diseases, 2020)
Myxobolus cerebralis (Bivalvulida: Myxobolidae), the aetiological agent of salmonid whirling disease, was detected in 2 river basins of North Carolina during 2015, which initiated the largest spatial–temporal monitoring project for the disease ever conducted within the south‐eastern United States (focused mainly in eastern Tennessee and western North Carolina). A total of 2072 rainbow trout Oncorhynchus mykiss , 1,004 brown trout Salmo trutta and 468 brook trout Salvelinus fontinalis were screened from 113 localities within 7 river basins during June 2017 through October 2019. Infections were detected by pepsin–trypsin digest, microscopy and the species‐specific nested polymerase chain reaction (PCR) in 19 localities across 6 river basins. Myxospore morphology was indistinguishable from the published literature. In 2019, five rainbow trout that symptomatic for whirling disease (sloping neurocranium and lordosis) were captured and processed for histopathology. Myxospores were detected in the calvarial cartilage of two deformed trout with associated erosion of the cartilage consistent with reported whirling disease lesions. This is the first report of M. cerebralis in Tennessee and the first histologically confirmed cases of whirling disease in southern Appalachian (south‐eastern United States) rivers and streams and expands the distribution of M. cerebralis throughout western North Carolina and eastern Tennessee.

Comparison of Maternal and Embryonic Trace Element Concentrations in Common Thresher Shark (Alopias vulpinus) Muscle Tissue - Jessica Dutton; Vittoria M. Venuti (Bulletin of Environmental Contamination and Toxicology, 2019)

Editorial: Advances in the Biology and Conservation of Marine Turtles - Sara M. Maxwell; Annette C. Broderick; Peter H. Dutton; Sabrina Fossette-Halot; Mariana M. P. B. Fuentes; Richard D. Reina (Frontiers in Marine Science, 2019)

Long-term trends in the foraging ecology and habitat use of an endangered species: an isotopic perspective - Elizabeth D. Hetherington; Jeffrey A. Seminoff; Peter H. Dutton; Lisa C. Robison; Brian N. Popp; Carolyn M. Kurle (Oecologia, 2018)

Organic matter and nutrient inputs from large wildlife influence ecosystem function in the Mara River, Africa - Amanda L. Subalusky; Christopher L. Dutton; Laban Njoroge; Emma J. Rosi; David M. Post (Ecology, 2018)
Animals can be important vectors for the movement of resources across ecosystem boundaries. Animals add resources to ecosystems primarily through egestion, excretion, and carcasses, and the stoichiometry and bioavailability of these inputs likely interact with characteristics of the recipient ecosystem to determine their effects on ecosystem function. We studied the influence of hippopotamus excretion/egestion and wildebeest carcasses, and their interactions with discharge, in the Mara River, Kenya. We measured nutrient dissolution and decomposition rates of wildlife inputs, the influence of inputs on nutrient concentrations and nutrient limitation in the river and the influence of inputs on biofilm growth and function in both experimental streams and along a gradient of inputs in the river. We found that hippopotamus excretion/egestion increases ammonium and coarse particulate organic matter in the river, and wildebeest carcasses increase ammonium, soluble reactive phosphorus, and total phosphorus. Concentrations of dissolved carbon and nutrients in the water column increased along a gradient of wildlife inputs and during low discharge, although concentrations of particulate carbon decreased during low discharge due to deposition on the river bottom. Autotrophs were nitrogen limited and heterotrophs were carbon limited and nitrogen and phosphorus colimited upstream of animal inputs but there was no nutrient limitation downstream of inputs. In experimental streams, hippo and wildebeest inputs together increased biofilm gross primary production ( GPP) and respiration ( R ). These results differed in the river, where low concentrations of hippo inputs increased gross primary production ( GPP ) and respiration ( R ) of biofilms, but high concentrations of hippo inputs in conjunction with wildebeest inputs decreased GPP . Our research shows that inputs from large wildlife alleviate nutrient limitation and stimulate ecosystem metabolism in the Mara River and that the extent to which these inputs subsidize the ecosystem is mediated by the quantity and quality of inputs and discharge of the river ecosystem. Thus, animal inputs provide an important ecological subsidy to this river, and animal inputs were likely important in many other rivers prior to the widespread extirpation of large wildlife.

Late Holocene inter-annual temperature variability reconstructed from the δ 18 O of archaeological Ostrea angasi shells - S. Tynan; B. Opdyke; A. Dutton; M. Walczak (Australian Journal of Earth Sciences, 2017)

Advances in the Application of Genetics in Marine Turtle Biology and Conservation - Lisa M. Komoroske; Michael P. Jensen; Kelly R. Stewart; Brian M. Shamblin; Peter H. Dutton (Frontiers in Marine Science, 2017)

Anniston community health survey: Follow-up and dioxin analyses (ACHS-II)—methods - Linda S. Birnbaum; N. D. Dutton; C. Cusack; S. T. Mennemeyer; M. Pavuk (Environmental Science and Pollution Research, 2016)

Diseases of captive yellow seahorse Hippocampus kuda B leeker, pot‐bellied seahorse Hippocampus abdominalis L esson and weedy seadragon Phyllopteryx taeniolatus ( L acépède) - V LePage; J Young; C J Dutton; G Crawshaw; J A Paré; M Kummrow; D J McLelland; P Huber; K Young; S Russell; L Al‐Hussinee; J S Lumsden (Journal of Fish Diseases, 2015)
Seahorses, pipefish and seadragons are fish of the F amily S yngnathidae. From 1998 to 2010, 172 syngnathid cases from the T oronto Z oo were submitted for post‐mortem diagnostics and retrospectively examined. Among the submitted species were yellow seahorses Hippocampus kuda Bleeker ( n = 133), pot‐bellied seahorses Hippocampus abdominalis Lesson ( n = 35) and weedy seadragons Phyllopteryx taeniolatus ( L acépède; n = 4). The three most common causes of morbidity and mortality in this population were bacterial dermatitis, bilaterally symmetrical myopathy and mycobacteriosis, accounting for 24%, 17% and 15% of cases, respectively. Inflammatory processes were the most common diagnoses, present in 117 cases. Seven neoplasms were diagnosed, environmental aetiologies were identified in 46 cases, and two congenital defects were identified.

The ecology of sexual conflict: ecologically dependent parallel evolution of male harm and female resistance in Drosophila melanogaster - Devin Arbuthnott; Emily M. Dutton; Aneil F. Agrawal; Howard D. Rundle (Ecology Letters, 2014)
The prevalence of sexual conflict in nature, along with the potentially stochastic nature of the resulting coevolutionary trajectories, makes it an important driver of phenotypic divergence and speciation that can operate even in the absence of environmental differences. The majority of empirical work investigating sexual conflict's role in population divergence/speciation has therefore been done in uniform environments and any role of ecology has largely been ignored. However, theory suggests that natural selection can constrain phenotypes influenced by sexual conflict. We use replicate populations of Drosophila melanogaster adapted to alternative environments to test how ecology influences the evolution of male effects on female longevity. The extent to which males reduce female longevity, as well as female resistance to such harm, both evolved in association with adaptation to the different environments. Our results demonstrate that ecology plays a central role in shaping patterns of population divergence in traits under sexual conflict.

Why ant pollination is rare: new evidence and implications of the antibiotic hypothesis - Emily M. Dutton; Megan E. Frederickson (Arthropod-Plant Interactions, 2012)

Fusarium infection of maize and maize-based products and exposure of a rural population to fumonisin B 1 in Limpopo Province, South Africa - J.Z. Phoku; M.F. Dutton; P.B. Njobeh; M. Mwanza; M.A. Egbuta; C.A. Chilaka (Food Additives & Contaminants: Part A, 2012)

Oceanographic influences on the dive behavior of juvenile loggerhead turtles (Caretta caretta) in the North Pacific Ocean - Evan A. Howell; Peter H. Dutton; Jeffrey J. Polovina; Helen Bailey; Denise M. Parker; George H. Balazs (Marine Biology, 2010)

Tetranucleotide markers from the loggerhead sea turtle (Caretta caretta) and their cross-amplification in other marine turtle species - Brian M. Shamblin; Brant C. Faircloth; Mark G. Dodd; Dean A. Bagley; Llewellyn M. Ehrhart; Peter H. Dutton; Amy Frey; Campbell J. Nairn (Conservation Genetics, 2009)

Intra-community spatial variation of size-fractionated organic compounds in Long Beach, California - Margaret A. Krudysz; Steven J. Dutton; Gregory L. Brinkman; Michael P. Hannigan; Philip M. Fine; Constantinos Sioutas; John R. Froines (Air Quality, Atmosphere & Health, 2009)

Subjective assessment of chimpanzee (Pan troglodytes) personality: reliability and stability of trait ratings - Diane M. Dutton (Primates, 2008)

Spatial and temporal variation in distribution and protein ubiquitination for Mytilus congeners in the California hybrid zone - Jessica M. Dutton; Gretchen E. Hofmann (Marine Biology, 2008)

Natal homing in juvenile loggerhead turtles ( Caretta caretta ) - BRIAN W. BOWEN; ANNA L. BASS; SHAIO‐MEI CHOW; MEREDITH BOSTROM; KAREN A. BJORNDAL; ALAN B. BOLTEN; TOSHINORI OKUYAMA; BENJAMIN M. BOLKER; SHERYAN EPPERLY; ERIN LACASELLA; DONNA SHAVER; MARK DODD; et al. (Molecular Ecology, 2004)
Juvenile loggerhead turtles ( Caretta caretta ) from West Atlantic nesting beaches occupy oceanic (pelagic) habitats in the eastern Atlantic and Mediterranean, whereas larger juvenile turtles occupy shallow (neritic) habitats along the continental coastline of North America. Hence the switch from oceanic to neritic stage can involve a trans‐oceanic migration. Several researchers have suggested that at the end of the oceanic phase, juveniles are homing to feeding habitats in the vicinity of their natal rookery. To test the hypothesis of juvenile homing behaviour, we surveyed 10 juvenile feeding zones across the eastern USA with mitochondrial DNA control region sequences ( N = 1437) and compared these samples to potential source (nesting) populations in the Atlantic Ocean and Mediterranean Sea ( N = 465). The results indicated a shallow, but significant, population structure of neritic juveniles (Φ ST = 0.0088, P = 0.016), and haplotype frequency differences were significantly correlated between coastal feeding populations and adjacent nesting populations (Mantel test R 2 = 0.52, P = 0.001). Mixed stock analyses (using a Bayesian algorithm) indicated that juveniles occurred at elevated frequency in the vicinity of their natal rookery. Hence, all lines of evidence supported the hypothesis of juvenile homing in loggerhead turtles. While not as precise as the homing of breeding adults, this behaviour nonetheless places juvenile turtles in the vicinity of their natal nesting colonies. Some of the coastal hazards that affect declining nesting populations may also affect the next generation of turtles feeding in nearby habitats.

Forage and migration habitat of loggerhead ( Caretta caretta ) and olive ridley ( Lepidochelys olivacea ) sea turtles in the central North Pacific Ocean - Jeffrey J. Polovina; George H. Balazs; Evan A. Howell; Denise M. Parker; Michael P. Seki; Peter H. Dutton (Fisheries Oceanography, 2004)
Satellite telemetry from 26 loggerhead ( Caretta caretta ) and 10 olive ridley ( Lepidochelys olivacea ) sea turtles captured and released from pelagic longline fishing gear provided information on the turtles’ position and movement in the central North Pacific. These data together with environmental data from satellite remote sensing are used to describe the oceanic habitat used by these turtles. The results indicate that loggerheads travel westward, move seasonally north and south primarily through the region 28–40°N, and occupy sea surface temperatures (SST) of 15–25°C. Their dive depth distribution indicated that they spend 40% of their time at the surface and 90% of their time at depths

Catecholamine responses to high intensity cycle ergometer exercise: Body mass or body composition? - J. S. Baker; D. M. Bailey; J. Dutton; B. Davies (Journal of Physiology and Biochemistry, 2003)

Biological control of Chenopodium album L. in Europe - J. Netland; L.C. Dutton; M.P. Greaves; M. Baldwin; M. Vurro; A. Evidente; G. Einhorn; P.C. Scheepens; L.W. French (BioControl, 2001)

Dual X-ray absorptiometry detects disease- and treatment-related alterations of bone density in prostate cancer patients - Gillian L. Smith; Alan P. Doherty; Linda M. Banks; Jane Dutton; Iain W. Hanham; Timothy J. Christmas; Richard J. Epstein (Clinical & Experimental Metastasis, 2000)

Personality in Captive Chimpanzees: Use of a Novel Rating Procedure - Diane M. Dutton; Roger A. Clark; David W. Dickins (International Journal of Primatology, 1997)

Analysis of disproportionate replication of ribosomal DNA in Drosophila melanogaster by a microhybridization method - Barry Yedvobnick; Hallie M. Krider; F. Lee Dutton (Biochemical Genetics, 1980)